(untitled) (Vietnam Journal of Community Medicine, 2022)
Objectives: To determine the relationship between sperm chromatin dispersion test (SCD) parameters (DNA fragmentation index - DFI) and conventional semen parameters in male patients with infertility. Subjects and methods: A cross-sectional descriptive study was performed on 150 semen samples of male patients by masturbation at the Center for Assisted Reproduction and Andrology - Phu Tho Obstetrics & Pediatrics Hospital. Evaluation of semen parameters according to WHO (2021) and determination of sperm DNA fragmentation index by SCD method. Results: A significant negative association between DFI with: Sperm density (r = -0.405, p<0.001), Sperm Mobility (r = - 0.30 và p < 0.001), Vitality (r = - 0.31 và p < 0.001), Sperm Morphology (r = -0.456 và p = <0.001). There is no difference in the degree of sperm fragmentation by age, time to abstain from ejaculation, ejaculate volume, pH. Conclusion: SCD Parameters had a significant negative association with: Sperm density, Mobility Sperm, Vitality, Sperm Morphology. No correlation was found between DFI-SCD with: Age, time to abstain from ejaculation, pH.